KEARIFAN LOKAL DI ERA INDUSTRIALISASI 4.0 DAN SOCIETY 5.0 DALAM PERSPEKTIF HUKUM - Taufik Wijoseno; Waskitara, Wisnu; Vivi Yulianigrum, Aulia (ANDREW Law Journal, 2024)
This research explores the role of local wisdom in maintaining national identity in the midst of globalization and the industrial revolution 4.0 and the impact of Society 5.0 developments on the preservation of local wisdom in Indonesia. Using a normative research method with an analytical descriptive approach, this research examines various legal regulations and related doctrines. The results show that local wisdom acts as a fortress in maintaining national identity, with adaptation to new technology being the key to success. Society 5.0 offers opportunities and challenges in preserving local traditions, requiring a comprehensive strategy to integrate technology without eroding cultural values. This study concludes that the preservation of local wisdom and national identity requires cooperation between the government, community, and stakeholders, as well as continuous education and adaptation to global changes. Suggestions for future research are to deepen the study of the implementation of technology in preserving local culture and strengthening national identity.